Arnold O. Beckman and Ronald Reagan - Studio One Professional Photography (1971)
Dr. Arnold O. Beckman (1900-2004) invented the first commercially successful electric pH meter in 1934 and thus began a long career manufacturing scientific and medical instruments with National Technical Laboratories, Arnold O. Beckman, Inc., and Beckman Instruments. Although his businesses operated world-wide, they began and their headquarters remained in California. After his retirement he devoted his life to philanthropy and specifically supporting scientific innovation. At the time of this photograph, Ronald Reagan was serving as governor of the state of California. He would go on to serve as the 40th President of the United States from 1981 to 1989.
Keywords: Reagan, Ronald; Beckman, Arnold O.; Presidents; Governors--U.S. states